hey Please simplify: (2x-1) square root 2x-1 thanks
Last edited by mr fantastic; Jul 18th 2009 at 03:53 AM. Reason: Changed post title, wrote the question that should have accompanied the expression
Follow Math Help Forum on Facebook and Google+
$\displaystyle = (2x - 1)\sqrt{(2x + 1)}$ $\displaystyle = \sqrt{((2x + 1)}(2x - 1)^2)$ $\displaystyle = \sqrt{((2x + 1)}(4x^2 - 4x + 1))$ $\displaystyle = \sqrt{(8x^3 - 8x^2 + 2x + 4x^2 - 4x + 1)}$ $\displaystyle = \sqrt{(8x^3 - 4x^2 - 2x + 1)}$
The answer is (2x-1)^3/2 at the back of the book
Originally Posted by smmmc The answer is (2x-1)^3/2 at the back of the book That's because A Beautiful Mind misread the problem. $\displaystyle (2x - 1)\sqrt{2x - 1}$ $\displaystyle \begin{aligned} &= (2x - 1)(2x - 1)^{1/2} \\ &= (2x - 1)^{3/2} \end{aligned}$ 01
View Tag Cloud